Feasibility of trans-horizon, high-capacity maritime wireless backhaul communication link - Zaidi, K.S. (IEEE Computer Society, 2014)
This paper discusses the feasibility of a high capacity, long range and low transmit power maritime wireless communication link over Sea using evaporation duct. Wireless backhaul gives a low cost solution for access to remote areas with difficult terrain and accessibility to install any wired link. Long-range backhaul network with high capacity and reliability is limited to line-of-sight (LOS) distances requiring high antenna towers and very high transmit energy power for further increase in range. Experimental results show the feasibility of a long-range, non-line-of-sight (NLOS) wireless backhaul communication link over Malaysian Sea. Low Transmit power used to achieve long-range distance proves this technology as highly Energy efficient. A mirror image of a high-capacity MIMO-OFDM-like system used on land can be envisaged on Sea to provide similar services at even trans-horizon distances. Â© 2014 IEEE.